Glucagonoma-associated dilated cardiomyopathy refractory to somatostatin analogue therapy. (5th March 2019) - Barabas, Michal; Huang-Doran, Isabel; Pitfield, Debbie; Philips, Hazel; Goonewardene, Manoj; Casey, Ruth T; Challis, Benjamin G
Summary: A 67-year-old woman presented with a generalised rash associated with weight loss and resting tachycardia. She had a recent diagnosis of diabetes mellitus. Biochemical evaluation revealed elevated levels of circulating glucagon and chromogranin B. Cross-sectional imaging demonstrated a pancreatic lesion and liver metastases, which were octreotide-avid. Biopsy of the liver lesion confirmed a diagnosis of well-differentiated grade 2 pancreatic neuroendocrine tumour, consistent with metastatic glucagonoma. Serial echocardiography commenced 4 years before this diagnosis demonstrated a progressive left ventricular dilatation and dysfunction in the absence of ischaemia, suggestive of glucagonoma-associated dilated cardiomyopathy. Given the severity of the cardiac impairment, surgical management was considered inappropriate and somatostatin analogue therapy was initiated, affecting clinical and biochemical improvement. Serial cross-sectional imaging demonstrated stable disease 2 years after diagnosis. Left ventricular dysfunction persisted, however, despite somatostatin analogue therapy and optimal medical management of cardiac failure. In contrast to previous reports, the case we describe demonstrates that chronic hyperglucagonaemia may lead to irreversible left ventricular compromise. Management of glucagonoma therefore requires careful and serial evaluation of cardiac status. Learning points: In rare cases, glucagonoma may present with cardiac failure as the dominant feature. Significant cardiac impairment may occur in the absence of other features of glucagonoma syndrome due to subclinical chronic hyperglucagonaemia. A diagnosis of glucagonoma should be considered in patients with non-ischaemic cardiomyopathy, particularly those with other features of glucagonoma syndrome. Cardiac impairment due to glucagonoma may not respond to somatostatin analogue therapy, even in the context of biochemical improvement. All patients with a new diagnosis of glucagonoma should be assessed clinically for evidence of cardiac failure and, if present, a baseline transthoracic echocardiogram should be performed. In the presence of cardiac impairment these patients should be managed by an experienced cardiologist.